Can the Magmatic Conditions of the Martian Nakhlites be Discerned via Investigation of Clinopyroxene and Olivine Intracrystalline Misorientations?. Issue 6 (4th June 2022) - Griffin, S.; Daly, L.; Piazolo, S.; Forman, L. V.; Cohen, B. E.; Lee, M. R.; Trimby, P. W.; Baumgartner, R. J.; Benedix, G. K.; Hoefnagels, B.
Abstract: Deformation is a near ubiquitous process that is observed within nearly all naturally forming rocks. Electron backscatter diffraction (EBSD) is a technique that enables slip‐systems (a form of plastic deformation) to be inferred from intracrystalline misorientations at a comparable scale to the representative CPO analysis (≥300 crystals for the nakhlites). Extensive laboratory and studies on naturally occurring samples have identified preferential mantle condition extrinsic parameters for specific slip‐system signatures within olivine and clinopyroxene. Intracrystalline misorientation patterns for olivine and augite (high Ca‐clinopyroxene) for 16 different Martian nakhlite meteorites (21 sections) were analyzed and assessed against these known parameters. Investigation of high and low deformation regions within the nakhlites revealed a shift in intracrystalline misorientation patterns for 10 of the 21 sections. Interpreted as both shock (high deformations) and emplacement (low deformation) signatures, the observed variations in deformation patterns for the two main regimes of deformation indicate heterogeneous sampling of the nakhlite source crater. Our findings indicate that shock deformation is prevalent throughout the nakhlites, and that great care needs to be taken when interpreting intracrystalline misorientations of crystals within apparent lower deformation regions. Plain Language Summary: Clinopyroxene and olivine are important minerals for studying igneous processes on Mars and Earth (from the surface to the upper mantle). Here, clinopyroxene and olivine intracrystalline misorientation patterns—deformational movement within a crystal—were investigated in a group of meteorites from Mars using the specialist microscopic technique of electron backscatter diffraction (EBSD). The nakhlites are mafic rocks representing the largest collection of rocks from a singular—but as yet unknown—location on Mars. Combined intracrystalline misorientation patterns for both olivine and clinopyroxene reveal nine different shock deformation signatures for the nakhlites indicating that they were sourced from multiple locations within the ejection crater. Nonshock related deformation can also be observed but tends to be masked by the dominance of shock deformation features even in low deformation regions. Key Points: Electron backscatter diffraction reveals shock‐derived deformation to mask nonshock deformation even in low deformation regions in the nakhlites Intracrystalline misorientation patterns indicate nine distinct derived deformation signatures for 16 nakhlites Intracrystalline misorientation patterns are identified within low deformation regions interpreted as emplacement deformation